548 Prevalence of frailty, pre-frailty and geriatric syndromes in people aged 60 or more that use the Cofrentes spa: a pilot study (Balneo and PRM Research Journal, 2024)
A longevity and balneotherapy treatment program has been initiated at the Cofrentes Medical Spa, including the development of the Rosita Longevity App. The objective of this study is to determine the health profiles (degree of frailty and pre-frailty) by means of Fried Frailty Phenotype questionnaire and the prevalence of geriatric syndromes in people over 60 doing balneotherapy at the spa, considering that the thermal environment is an ideal place to treat these types of syndromes and to delay their progress. Thermal/spa facilities often receive older patients with osteo-articular and musculoskeletal conditions. To assess the grade of the functionality, quality of life, depression, nutritional risk, cognitive state, insomnia, and the risk of falls, specific questionnaires were used. Out of a total of 43 participants, 30 were women (69.7%), and 22 older than 70 y (51.1%). There were 2 frail (4.6%) and 20 prefrail (46.5%). Conclusions: more than half of the people older than 60 who visit the Cofrentes spa present a functionality deficit condition. Women present a lower quality of life than men. The more affected items in the prefrail population were grip strength and physical activity. Health Resort Medicine is an ideal place to detect these aspects.Keywords: frailty, elderly, geriatric assessment, health resort medicine, balneology